First-trimester biomarkers and ultrasound biometries in relation to growth discordance in monochorionic diamniotic twins. (31st December 2023) - Løppke, Frederikke Bang; Schou, Katrine Vasehus; Ekelund, Charlotte Kvist; Rode, Line; Tabor, Ann; Sundberg, Karin
Abstract: Objective: The aim of this study was to investigate the association and predictive value between intertwin discordance in first trimester biometries crown-rump length (CRL) and nuchal translucency (NT), and the first trimester biochemical markers PAPP-A and free β-hCG in relation to birth weight discordance (BWD) ≥25% in monochorionic diamniotic (MCDA) twin pregnancies. Methods: First trimester screening information and pregnancy outcome data on MCDA twin pregnancies with delivery from July 2008 to July 2017 were retrieved from the Danish Fetal Medicine Database. CRL discordance was divided into: <10% (reference group) and ≥10%. NT discordance was divided into: <20% (reference group) and ≥20%. The twin pregnancies were classified according to BWD into the following groups: <10% (reference group), 10–24.9%, and ≥25% including cases undergoing umbilical cord occlusion due to selective fetal growth restriction (sFGR). The twin pregnancies with the most severe BWD (BWD ≥25%) were subdivided into three groups including cases with only one growth-restricted (<10th centile) infant defined as sFGR, and cases where both twins were <10th centile. Median multiples of the median (MoM) values of PAPP-A and free ß-hCG were compared with the group with BWD <10% using the Wilcoxon two-sample test. The ability of CRL discordance and NT discordance to predict BWD ≥25% was examined by the area under the receiver operator characteristic (ROC) curve. Results: A total of 762 MCDA pregnancies were included. The proportion of pregnancies with CRL discordance ≥10% and NT discordance ≥20% was significantly higher in the group with severe BWD discordance (27.0% vs. 4.7% ( p  < 0.001) and 40.9% vs. 23.9% ( p  = 0.001), respectively). When examining the three subgroups of severe BWD, we found a significantly higher percentage of pregnancies with CRL discordance ≥10% in the group where umbilical cord occlusion was performed (52.6% vs. 4.7% in the group with BWD <10% ( p  < 0.001)) and in the group of BWD ≥25% with sFGR (21.7% vs . 4.7% ( p  < 0.001)). Additionally, a significantly higher percentage of pregnancies with NT discordance ≥20% was found in the group where umbilical cord occlusion was performed (52.6% vs. 23.9% ( p  = 0.005)) and in the group with both twins <10th centile (66.7% vs. 23.9% ( p  = 0.003)). No statistically significant differences were found when comparing levels of PAPP-A and free β-hCG MoMs with the group with BWD <10%. In ROC curves, CRL discordance yielded an AUC for prediction of BWD ≥25% of 0.70 (95% CI 0.63–0.76), and for NT discordance AUC was 0.59 (95% CI 0.52–0.66)). OR for any BWD ≥ 25% was 6.7 (95% CI 3.8–12.0) for pregnancies with a CRL discordance ≥10% compared to pregnancies with a CRL discordance <10%. Conclusions: This study shows that a discordance in CRL and NT in MCDA twins are both significantly associated with development of BWD. The most important predictor remains CRL discordance ≥10%, thereby suggesting the unequal growth pattern in many cases with BWD is evident already in the first trimester of the pregnancy. No association was found between first trimester biochemical markers and severe BWD.